Marketing automation supporting sales - Sandell, Niko (2016)
The past couple of decades has been a time of major changes in marketing. Digitalization has become a permanent part of marketing and at the same time enabled efficient collection of data. Personalization and customization of content are playing a crucial role in marketing when new customers are acquired. This has also created a need for automation to facilitate the distribution of targeted content. As a result of successful marketing automation more information of the customers is gathered and at the same time, the work of sales force will be facilitated due to a larger amount of information.